CLINICAL ANATOMY OF STOMAL AND NON-TRANSIT AREAS OF COLON AFTER OBSTRUCTIVE RESECTION AND ITS ROLE IN RECONSTRUCTIVE SURGERIES IN DIFFERENT MODIFICATIONS - B. К. Gibert; I. A. Matveev; N. A. Borodin; A. I. Matvee; D. Т. Hasia; F. Sh. Aliev (Вестник хирургии имени И.И. Грекова)
OBJECTIVE. The objective of the study is to research the anatomical features of stomal and non-transit areas of colon after obstructive resections and ways of preoperative determination of diastase liquidation for choosing a rational type of reconstructive surgery.MATERIAL AND METHODS. Topographo-anatomical features of stomal and non-transit areas of colon of 197 terminal colostomy patients with reconstruction surgery were examined. Their impact on conduction of reconstructive surgeries from midline, parastomal incision and laparoscopic assisted method were also studied.RESULTS. The objects of anastomosis can be located in the same, in neighboring or in separate abdominal areas that determine diastasis size between them. 74 (37.56 %) patients had parastomal area localization of stump. 93 (47.21 %) patients had stump located in adjacent areas and 30 (15.23 %) had a stump located in separate abdominal areas. Besides the location of anastomosed segments, mobility of bowels also has a great impact on conjunction which determines by the place of stump and stoma formation. The techniques of preoperative determination of reconstruction possibility of passage continuity without colon mobilization were developed taking into account these anatomical features.CONCLUSION. Localization of anastomosing objects, their length and mobility allowedreconstructing bowel continuity of 167 patients (84. 77 %) without coloplastics. Possibility of preoperative determination of reconstruction of bowel continuity without colon mobilization objectifies the choice of rational reconstructive surgery method.